2022
DOI: 10.1002/lary.30441
|View full text |Cite
|
Sign up to set email alerts
|

Extent of Surgery for Follicular Thyroid Carcinoma

Abstract: Objectives To examine the association between the extent of surgery and overall survival in follicular thyroid cancer (FTC) patients. Study Design Retrospective analysis of the National Cancer Database (NCDB). Methods Patients who underwent surgical intervention for FTC from 2004 to 2015 were selected. Patients were >18 years old, with tumor size 1–4 cm, no other malignancies, and >0 follow up time. Patients were divided into two cohorts based on extent of surgery: lobectomy (≥1 lobe resected) and thyroidectom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…It has also been suggested that nodule size and histologic subtype are factors influencing prognosis, such that patients with nodules >4 cm and widely invasive FTC have a worse prognosis. Studies on the influence of surgical method on the prognosis of FTC patients do not have the same results, some believe that the prognosis of unilateral thyroidectomy is similar to that of total lobectomy, while others prefer a better prognosis for total lobectomy 3,16–20 . Therefore, the choice of surgical method by surgeons is still controversial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been suggested that nodule size and histologic subtype are factors influencing prognosis, such that patients with nodules >4 cm and widely invasive FTC have a worse prognosis. Studies on the influence of surgical method on the prognosis of FTC patients do not have the same results, some believe that the prognosis of unilateral thyroidectomy is similar to that of total lobectomy, while others prefer a better prognosis for total lobectomy 3,16–20 . Therefore, the choice of surgical method by surgeons is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the influence of surgical method on the prognosis of FTC patients do not have the same results, some believe that the prognosis of unilateral thyroidectomy is similar to that of total lobectomy, while others prefer a better prognosis for total lobectomy. 3 , 16 , 17 , 18 , 19 , 20 Therefore, the choice of surgical method by surgeons is still controversial.…”
Section: Introductionmentioning
confidence: 99%